1986
DOI: 10.1007/bf00333277
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bacterial segregation by early functions of phage Mu and association of replication protein B with the inner cell membrane

Abstract: Infection of Mu-sensitive bacteria with a recombinant lambda phage that carries the EcoRI.C fragment from the immunity end of wild type Mu DNA causes filamentous growth. Transmission electron microscopy revealed that the cell-division cycle was inhibited at, or prior to, the initiation of septation. The filamentation does not occur after infection of Mu-immune bacteria or after infection with a phage carrying the same EcoRI.C fragment, but with an IS1 insertion in gene B of Mu, showing that either gpB and/or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…High-level expression of the Mu B protein involved in transposon target site selection has been shown to be lethal to E. coli and also leads to filament formation (4). The Mu B protein also fractionates with the inner cell membrane (4). A number of other bacterial IS Tnps also lead to cell killing and filamentation when overexpressed (1).…”
Section: Discussionmentioning
confidence: 99%
“…High-level expression of the Mu B protein involved in transposon target site selection has been shown to be lethal to E. coli and also leads to filament formation (4). The Mu B protein also fractionates with the inner cell membrane (4). A number of other bacterial IS Tnps also lead to cell killing and filamentation when overexpressed (1).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, not only does overproduction of the MuB protein cause the same cell killing phenotype as that of Tn5 Tnp but Boeckh et al (7) have reported that MuB also associates with the inner cell membrane. Thus, we conclude that Tn5 Tnp (and perhaps MuB) overproduction killing is correlated with inner cell membrane association.…”
Section: It Has Been Reported That Tn5mentioning
confidence: 99%
“…It has long been known that a T4 deoxynucleotide synthetase is involved in supplying immediate DNA precursors to the replisome (12,79,97) and that one of the enzymes in this complex, dCTPase, is also encoded by the oriA region (88). These include the dnaB protein of B. subtilis (46,118), the dnaJ and dnaK proteins of E. coli (144,145,147), the dnaA protein of E. coli (104,105,142), the B protein of phage Mu (8,103) (see below), possibly the P initiation protein of phage A (146), and possibly the trfA initiation protein of plasmid RK2 (62). These include the dnaB protein of B. subtilis (46,118), the dnaJ and dnaK proteins of E. coli (144,145,147), the dnaA protein of E. coli (104,105,142), the B protein of phage Mu (8,103) (see below), possibly the P initiation protein of phage A (146), and possibly the trfA initiation protein of plasmid RK2 (62).…”
Section: Bacteriophage Amentioning
confidence: 99%
“…In addition, the copy number of the minichromosome varied considerably from population to population, which implies that there was an abnormality in control mech anisms, possibly related to incompatibility functions (89). New developments have in volved DNA binding studies with specific membrane proteins or membrane preparations (41, 55,61,66,69,81,120,132,133), striking correlations between defects in the conformation or activity of the DNA/membrane com plex and inhibition of initiation (51,92,130,139), further analysis of the synthetic capabilities of DNA/membrane complexes (6,7,22,24,25,27,62,67,69,143), and identification or recognition of specific genes that may code for membrane proteins involved in DNA replication (8,46,87,88,103,105,118,145,146). Yoshimoto et al (141) found that replicative intermediates of an OriC plasmid associated with the outer membrane of E. coli were free of globular (membrane) proteins, whereas the chromosomal oriC was associated with such components.…”
Section: Introductionmentioning
confidence: 99%